Transferring R&D Outputs to Industry: Strategies of R&D Organizations - Stanislav Zaichenko (Foresight and STI Governance)
Stanislav Zaichenko — Senior Research Fellow, Laboratory for Economics of Innovation, Institute for Statistical Studies and Economics of Knowledge, National Research University — Higher School of Economics. E-mail: szaichenko@hse.ru. Address: National Research University — Higher School of Economics, 20, Myasnitskaya str., Moscow, 101000